DEVELOPMENT STRATEGIC OF SIMULATOR TECHNOLOGY 4.5 GENERATION FIGHTER AIRCRAFT FOR SUPPORTING NATIONAL DEFENSE SYSTEM - Faishal Irfan; Romie Oktovianus Bura; Heri Yansyah (The Republic of Indonesia Defense University, 2020)
The fighter aircraft project is one of the defense and security equipment (alpalhankam or alat peralatan pertahanan dan keamanan) priority programs contained in the defense industry roadmap. Indonesia and South Korea undertook a joint development program in developing 4.5 generation fighter aircraft. However, Indonesia experiences several obstacles in the development of fighter aircraft, one of which is the ability of disparity and mastery of fighter technology. One of the critical components used as one of the development programs is simulator technology development. Mastery of simulator technology can improve the ability of Technology Readiness Level (TRL) from technology development fighter aircraft and can cause multiplier effects in other fields. Therefore we need a development strategy that is appropriate for the development of simulator technology. This study aims to analyze and define the benchmark level of performance or from the critical components which will then be used as a reference for the development strategy of the 4.5 generation fighter simulator for joint development projects. The method used in this study is a mixed-method with an approach system engineering uses quality function deployment tools and Critical Technology Element (CTE) technology assessment to identify which CTE then used as a reference strategy for the development of fighter simulator technology. The results of the study show that there are several CTE values along with simulator technology performance scores, among others mission 92.5%, data 83.56%, motion 52.51%, and strategic options that can be used in the technological development of fighter simulator generation 4.5 such as strategic joint development, self-development, and local content/offset.